Pengenalan APOCIL (Apoteker Cilik) dan Edukasi Pentingnya Vitamin pada Anak di SDN Badurame Turi Lamongan - Irma Susanti; Tusamma Salsabiila; Novely Dwita Ramadhani; M. Muflih Zaki Al-Hadi; Annisa Ariantika; Gharizah Raisa Aqila; Sintya Shafa Qotrunnida (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The role of pharmacists is very important in providing education about medicines, especially vitamins. The introduction of vitamins at elementary school level is one of the duties of a pharmacist. This service was carried out at SDN Badurame with the theme "Introducing Apocil (Little Pharmacist) and Education on the Importance of Vitamins to Children at SDN Badurame Turi Lamongan". The aim of introducing vitamins is to reduce errors in vitamin consumption that often occur at the adolescent level. By introducing it from elementary school level, it is hoped that it can educate students that medicine is poison and can only be used according to certain conditions, type of disease and dosage. The target of this activity is students in grades 4, 5 and 6 at SDN Badurame. Implementation of activities begins with the preparation stage, namely making the required instruments (posters and attendance lists). Followed by the implementation stage, namely educational activities in the form of delivering material, demonstrations and questions and answers. There are 2 materials provided, namely Introduction to the Pharmacist Profession and Vitamin Education. The results of this service activity showed that students were able to receive learning material well. This was proven during demonstration activities and question and answer sessions, all students were able to demonstrate and answer all questions well and correctly.